Utilising buckling modes for the determination of the anisotropic mechanical properties of As2S3 nanosheets. Issue 21 (18th May 2022) - Dong, Ming; Sun, Yiwei; Dunstan, David J.; Papageorgiou, Dimitrios G.
Abstract : The mechanical properties of As2 S3 were measured by utilising buckling modes. The results make As2 S3 one of the softest, polarization-dependent anisotropic 2D materials. Abstract : The mechanical properties and interfacial behaviour of two-dimensional (2D) materials are crucial for their use in a number of technological applications. In this paper, two buckling modes, wrinkling and buckling delamination, were used to characterize the mechanics of As2 S3 nanosheets. The plane-strain moduli of As2 S3 nanosheets along the armchair (AC) and zigzag (ZZ) directions were determined via periodic wrinkles to be 16.7 ± 0.5 GPa and 51.5 ± 1.9 GPa, respectively. This is one of the largest reported anisotropies of in-plane mechanical properties among 2D materials. Using the delaminated buckles, the adhesion energy of few-layer As2 S3 nanosheets on silicon and polymer (polymethyl methacrylate and polydimethylsiloxane) substrates was determined to be 0.110 ± 0.006 and 0.022 ± 0.002 J m −2, respectively. A buckling mode map for As2 S3 nanosheets on different substrates is presented.